Hydraulic response in flooded stream networks. Issue 1 (12th January 2015) - Åkesson, Anna; Wörman, Anders; Bottacin‐Busolin, Andrea
Abstract: Average water travel times through a stream network were determined as a function of stage (discharge) and stream network properties. Contrary to most previous studies on the topic, the present work allowed for streamflow velocities to vary spatially (for most of the analyses) as well as temporally. The results show that different stream network mechanisms and properties interact in a complex and stage‐dependent manner, implying that the relative importance of the different hydraulic properties varies in space and over time. Theoretical reasoning, based on the central temporal moments derived from the kinematic‐diffusive wave equation in a semi‐2‐D formulation including the effects of flooded cross sections, shows that the hydraulic properties in contrast to the geomorphological properties will become increasingly important as the discharge increases, stressing the importance of accurately describing the hydraulic mechanisms within stream networks. Using the physically based, stage‐dependent response function as a parameterization basis for the streamflow routing routine (a linear reservoir) of a hydrological model, discharge predictions were shown to improve in two Swedish catchments, compared with a conventional, statistically based parameterization scheme. Predictions improved for a wide range of modeled scenarios, for the entire discharge series as well as for peak flow conditions. The foremost novelty of the study lies in that the physically based response function for a streamflow routing routine has successfully been determined independent of calibration, i.e., entirely through process‐based hydraulic stream network modeling. Key Points: Different parameterization methods for a streamflow routine were performed Physically based effects of stage‐dependency improved the peak flow predictions Stage dependency of geomorphological and hydraulical dispersion mechanisms